Pressure Distribution at Inner Surface of Selected Pelton Bucket for Micro Hydro - K.C., Binaya; Thapa, Bhola (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Four different Pelton bucket contours have been designed at Kathmandu University, namely DB01, DB02, DB03, and DB04. The primary aim of this study is to provide a detailed experimental analysis of the pressure distribution in these four different bucket contours, along with comparison to the commonly used ITDG bucket contour. The head and flow rate have been maintained constant during the test period. The pressure distribution around the inner surface of the bucket has been measured at three different angles of the bucket to the jet incidence: 0 degrees (normal to the jet), +15 degrees (incline away from the jet), and -15 degrees (incline towards the jet), considering extreme contact conditions by the jet. The test has been carried out for the stationary bucket. The pressure is measured in 20 orthogonal grid points of size 10mm x 10mm. The bucket is drilled normal to the surface on each pressure intake points. Fine copper pipes of 5mm diameter are fitted from the external surface of each orifice as pressure taps. Transparent PVC pipes are fitted to each pressure point for measuring pressure head in terms of water height. The bucket DB02 with elliptical section has been found with uniform pressure distribution. This profile had shown better performance in terms of torque. The pressure distribution inside the bucket DB02 has matched the flow pattern.